FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN JAMBAN KELUARGA DAN KEJADIAN DIARE DI DESA TUALANG SEMBILAR KECAMATAN BAMBEL KABUPATEN ACEH TENGGARA TAHUN 2012 - Rahma Ayu Pebriani; Surya Dharma; Evi Naria (Lingkungan dan Kesehatan Kerja, 2013)
Factors Related With the Use of Family Latrines and the Incidence of Diarrhea in the Village of Tualang Sembilar Bambel Southeast Aceh District in 2012. One of the health efforts by community  is to prevation basic sanitation facilities. One of the  basic sanitation facilities in the community latrine. For that, keep in mind the factors related with the use of latrines. One of the diseases that can be generated is a diarrheal disease. Diarrhea can be defined absolutely or relatively. Absolute diarrhea is defined as more than five bowel movements a day or liquid stools. Relative diarrhea is defined as an increase in the number of bowel movements per day or an increase in the looseness of stools compared with an individual's usual bowel habit. In diarrhea, bowel patients more than usual, the diarrhea may be defined as a bowel movement more than three times. The purpose of this study is the to analysis factors related with the use of latrines and the incidence of diarrhea in the village of Tualang Sembilar Bambel Southeast Aceh district in 2012. The method used in this research is  analytic descriptive research with cross sectional design. The samples in this study were 71 samples using random sampling technic , the sampling technique is done by random sampling. The results showed that 46.5% of respondents did not work; 33.8% of low-income respondents; 64.8% of respondents knowledgeable about ; 66.2% of respondents are not good; 52.1% latrine conditions do not qualify; 52, 1% use pit latrines 40.8% no 59.2% 53.5% instead diarrhea diarrhea 46.5%. The results of the statistical test using Chi-square tests were , knowledge, attitudes, and conditions of latrines have a significant relationship with the use of latrines and diarrhea. For people living in the village of Tualang Sembilar Bambel Southeast Aceh district home use the latrines when defecating to prevent diarrhea. Keywords: Knowledge, Attitudes, Usage Latrines, Diarrhea